[Encyclopedia] Pharmaceutical Manufacturing Encyclopedia (3rd edition) - William Andrew Publishing, William Andrew (William Andrew Publishing, 2007)
This industry standard database on pharmaceutical manufacturing processes has been completely updated to include FDA drugs approved up to the summer of 2004.The database gives details for the manufacture of 2226 pharmaceuticals that are being marketed as a trade-named product somewhere in the world. Each entry includes:Therapeutic functionChemical and common nameStructural FormulaChemical Abstracts Registry numberTrade name, manufacturer, country, and year introducedRaw MaterialsManufacturing ProcessIn addition, references are also cited under each drug's entry to major pharmaceutical works where additional information can be obtained on synthesis and the pharmacology of the individual products.